2005
DOI: 10.1080/13880200500220805
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Benzoyl Peroxide–Induced Cutaneous Oxidative Stress, Toxicity, and Ear Edema in Mice byNardostachys jatamansi.

Abstract: Recent years have shown considerable efforts to identify new chemopreventive agents that could be of clinical value. In the current study, modulatory effect of Nardostachys jatamansi (Jones) DC on benzoyl peroxide-induced oxidative stress, toxicity, and ear edema is investigated. Pretreatment with jatamansi at doses of 2.5 and 5 mg=kg body weight in acetone prior to the application of benzoyl peroxide (20 mg=animal per 0.2 ml acetone) resulted in significant inhibition of benzoyl peroxide-induced cutaneous oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…BPO exposure in mice has been demonstrated to deplete antioxidant defence and increase lipid peroxidation (e.g. Ali, Dua, Siddiqui, Sultana, & Rafiullah, 2005; Sharma & Sultana, 2004). To determine a suitable concentration of the free radical initiator BPO (Slaga et al., 1981), we first ran a range finding experiment with five concentrations (control, 1, 2, 5, 10 and 20 mg/L).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…BPO exposure in mice has been demonstrated to deplete antioxidant defence and increase lipid peroxidation (e.g. Ali, Dua, Siddiqui, Sultana, & Rafiullah, 2005; Sharma & Sultana, 2004). To determine a suitable concentration of the free radical initiator BPO (Slaga et al., 1981), we first ran a range finding experiment with five concentrations (control, 1, 2, 5, 10 and 20 mg/L).…”
Section: Methodsmentioning
confidence: 99%
“…Although the selected BPO concentration was in the same order of magnitude as those used in other studies (e.g. Ali et al., 2005; Sharma & Sultana, 2004) and not lethal during a 4‐week exposure during the range finding test, the exposure duration during the actual experiment was much longer (up to 37 days longer) and considerable mortality (up to 50%) due to BPO exposure was observed. As a consequence, it was not possible to accurately assess which of the BPO‐induced effects were really caused by oxidative stress and to what amount also other toxic effects played a role.…”
Section: Methodsmentioning
confidence: 99%
“…3 Several biological effects of the extracts from this species were reported, such as stress remedies, nervous headaches, epilepsy, intestinal colic, improving learning and memory and liver protection. [4][5][6][7] Besides, recent studies have showed chemical constituents of N. jatamansi possess positive anti-Alzheimer's disease activity. 8,9 To the best of our knowledge, previous phytochemical investigations on N. jatamansi led to the isolation of iridoids, sesquiterpenoids, and lignans.…”
Section: Introductionmentioning
confidence: 99%
“…27 An acetone extract of N. jatamansi has shown significant inhibition of benzoyl peroxide-induced cutaneous oxidative stress, toxicity, and ear edema in mice. 28 It has also been reported to possess protective activity in 6-hydroxydopamine-induced, parkinsonism in rats. 29 These pharmacological properties of N. jatamansi prompted us to evaluate its efficacy in haloperidol-induced parkinsonism.…”
Section: Dovepressmentioning
confidence: 99%